2015
DOI: 10.1590/s1516-8913201500479
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine sexual differentiation: biosyntesis and action of sexual steroid hormones

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 32 publications
0
9
0
10
Order By: Relevance
“…Association constants for complexes of 81 were determined and compared to those of simple, non-capped zinc porphyrin. In CDCl 3 , it was found that nitrogen bases, such as 4-hydroxypyridine, which can undergo both metal-amine and H-bonding interactions, formed a more stable complex with 81 than with the simple metalloporphyrin.…”
Section: Bile Acid-porphyrin Conjugatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Association constants for complexes of 81 were determined and compared to those of simple, non-capped zinc porphyrin. In CDCl 3 , it was found that nitrogen bases, such as 4-hydroxypyridine, which can undergo both metal-amine and H-bonding interactions, formed a more stable complex with 81 than with the simple metalloporphyrin.…”
Section: Bile Acid-porphyrin Conjugatesmentioning
confidence: 99%
“…Cholesterol is the precursor of the bile acids in the liver and the starting material for the biosynthesis of steroid hormones. Steroid hormones influence sex differentiation, support reproduction and regulate a wide variety of develop -mental and physiological processes from fetal life to adulthood [3]. Steroid biosynthesis is an anabolic pathway, which produces steroids from simple precursors via unique biosynthetic pathways.…”
Section: Introductionmentioning
confidence: 99%
“…O equilíbrio hormonal entre andrógenos e estrógenos é essencial para o adequado desenvolvimento das características reprodutivas, tanto em machos como em fêmeas (SANTOS et al, 2015b). O letrozol é um composto altamente específico capaz de ocasionar uma desproporção na razão entre esses hormônios esteroides, uma vez que bloqueia a ação da enzima citocromo P450 aromatase sem afetar outras vias esteroidogênicas (BHATNAGAR, 2007).…”
Section: Revisão De Literaturaunclassified
“…O letrozol é um composto altamente específico capaz de ocasionar uma desproporção na razão entre esses hormônios esteroides, uma vez que bloqueia a ação da enzima citocromo P450 aromatase sem afetar outras vias esteroidogênicas (BHATNAGAR, 2007). Esta enzima, por sua vez, atua em diversos tecidos com capacidade esteroidogênica como gônadas e cérebro, biossintetizando estrógenos a partir dos andrógenos (SANTOS et al, 2015b).…”
Section: Revisão De Literaturaunclassified
“…Desordens na produção das enzimas esteroidogênicas e dos hormônios esteroides por elas sintetizados durante o processo de diferenciação sexual, desenvolvimento das gônadas e órgãos copulatórios, como os hemipênis, podem gerar espécimes intersexuadas (SANTOS et al, 2015). O desenvolvimento do hêmipênis ocorre em fêmeas de Squamata, como em anfisbenas (KASPEROVICZUS et.…”
Section: Introdução Geralunclassified